2018
DOI: 10.3961/jpmph.17.166
|View full text |Cite
|
Sign up to set email alerts
|

Family Members of Cancer Patients in Korea Are at an Increased Risk of Medically Diagnosed Depression

Abstract: ObjectivesFamily members are often cancer patients’ primary source of social and emotional support and make a major contribution to how well patients manage their illness. We compared the prevalence of depression in the family members of cancer patients and the general population. MethodsThis study used the data from the fourth, fifth, and sixth rounds of the Korea National Health and Nutrition Examination Survey. The variable of interest was the presence of a cohabitating cancer patient in the family and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…First, family caregivers are primary and the most important source of support and directly affect quality of life, treatment, prognosis, and survival rates of patients with cancer. 10,11 Therefore, physical, emotional, and practical problems faced by family members are very significant issues. 10 Second, although family caregivers themselves suffer from physical (eg, fatigue and sleep disorders), psychological (eg, depression and guilt), economic (eg, medical expenses) and social aspects (eg, changes in lifestyle), family caregivers are often neglected and become invisible patients in practice and research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, family caregivers are primary and the most important source of support and directly affect quality of life, treatment, prognosis, and survival rates of patients with cancer. 10,11 Therefore, physical, emotional, and practical problems faced by family members are very significant issues. 10 Second, although family caregivers themselves suffer from physical (eg, fatigue and sleep disorders), psychological (eg, depression and guilt), economic (eg, medical expenses) and social aspects (eg, changes in lifestyle), family caregivers are often neglected and become invisible patients in practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Therefore, physical, emotional, and practical problems faced by family members are very significant issues. 10 Second, although family caregivers themselves suffer from physical (eg, fatigue and sleep disorders), psychological (eg, depression and guilt), economic (eg, medical expenses) and social aspects (eg, changes in lifestyle), family caregivers are often neglected and become invisible patients in practice and research. 12,13 More seriously, empirical evidence shows that depression and anxiety among family caregivers is more severe than that of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moreover, some studies have reported that the families of patients with cancer may experience emotional distress and depression. 34,35 Therefore, patients may avoid telling their families about invisible subjective symptoms like mental conflict or anxiety; the differences found here between patients and their families in recognizing invisible subjective symptoms may reflect this.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, there is a need to personalize this assessment in terms of the experience, capacity and context of the caregiver [ 12 ]. The burden that caregivers are subjected to can be related to the presence of endocrine, nutritional, and metabolic conditions, resulting largely from the social isolation, lack of free time, low quality of life, and even a deteriorating economic situation [ 13 , 14 , 15 , 16 , 17 ]. To measure this burden, there are some scales, being the Zarit Scale, the most used [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%